2005
DOI: 10.1152/ajplung.00199.2004
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback between secretory and cytosolic phospholipase A2 and their opposing roles in ovalbumin-induced bronchoconstriction in rats

Abstract: Negative feedback between secretory and cytosolic phospholipase A2 and their opposing roles in ovalbumin-induced bronchoconstriction in rats. Am J Physiol Lung Cell Mol Physiol 288: L523-L529, 2005. First published November 19, 2004 doi:10.1152/ajplung.00199.2004.-Phospholipase A2 (PLA2) hydrolyzes cell membrane phospholipids (PL) to produce arachidonic acid and lyso-PL. The PLA 2 enzymes include the secretory (sPLA 2) and cytosolic (cPLA2) isoforms, which are assumed to act synergistically in production of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 41 publications
10
36
0
Order By: Relevance
“…This hypothesis was strongly supported by our recent study with an experimental allergic bronchitis model in rats 15 which showed that ovalbumin (OVA) induced bronchoconstriction is associated with an increase in sPLA 2 and CysLT levels and suppression of cPLA 2 and PGE 2 levels. Furthermore, these processes were reversed by treatment with an extracellular sPLA 2 inhibitor (ExPLI), suggesting a pivotal role for sPLA 2 in the pathophysiology of allergy.…”
mentioning
confidence: 63%
“…This hypothesis was strongly supported by our recent study with an experimental allergic bronchitis model in rats 15 which showed that ovalbumin (OVA) induced bronchoconstriction is associated with an increase in sPLA 2 and CysLT levels and suppression of cPLA 2 and PGE 2 levels. Furthermore, these processes were reversed by treatment with an extracellular sPLA 2 inhibitor (ExPLI), suggesting a pivotal role for sPLA 2 in the pathophysiology of allergy.…”
mentioning
confidence: 63%
“…Recently, using an extracellular inhibitor of sPLA 2 s in a murine model of asthma, Offer et al 50 showed that sPLA 2 s induce primarily cysteinyl leukotriene generation, whereas cPLA 2 is mainly responsible for prostaglandin E 2 production. These results suggest that cPLA 2 s and sPLA 2 s might have opposing roles in asthma and that their selective inhibition could be a novel pharmacologic approach to modulate eicosanoid formation.…”
Section: Therapeutic Implications Of Spla 2 Inhibitors In Inflammatormentioning
confidence: 99%
“…Using specific inhibitors, it has been demonstrated that sPLA 2 and cPLA 2 play opposing roles in asthma pathophysiology with sPLA 2 s linked to the production of the bronchoconstrictor Cys-LT whereas cPLA 2 promotes the production of the bronchodilator PGE2. In cells that play a key role in asthma, namely, human eosinophils and basophils, PGE2 is produced from a cPLA 2 -linked pool [20,[22][23][24]. sPLA 2 s are found at high levels in bronchoalveolar lavage (BAL) fluid and bronchotracheal smooth muscle cells [25,26].…”
Section: Advances In Vascular Medicinementioning
confidence: 99%
“…In contrast, 12/15-lipoxygenase products are generally considered protective [18,19]. PGD2; thromboxane A2 (TXA2) and cysteinyl leukotrienes (cys-LTs) are reported to function as bronchoconstrictors while PGE2 is considered to act as bronchodilator [20].…”
Section: Introductionmentioning
confidence: 99%